N-doped self-supporting porous calcium ball ozone oxidation catalyst

By synchronously introducing metal and non-metal active components into porous calcium spheres formed by crosslinking sodium alginate and Ca2+, an N-doped self-supported porous calcium sphere ozone oxidation catalyst was designed, which solved the problem of difficult degradation of organic matter and inorganic salts in traditional technology in traditional technology, and achieved efficient and stable catalytic effect.

CN119657193AActive Publication Date: 2025-03-21BEIJING UNIV OF CHEM TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411663991.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-21
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the prior art, when treating salt-containing organic wastewater, it is difficult to effectively remove difficult-to-degrade organic matter and inorganic salts, resulting in inhibition of microbial activity and unsatisfactory treatment effect. At the same time, traditional supported metal-based catalysts have problems of catalyst instability and metal leaching during long-term use, resulting in secondary contamination.

Method used

An N-doped self-supported porous calcium sphere ozone oxidation catalyst was designed to form a porous carbon network by crosslinking sodium alginate with Ca2+, and the metal and non-metal active components were introduced simultaneously into the network to form an active center of metal-non-metallic synergistic catalysis.

Benefits of technology

This catalyst has the advantages of high catalytic activity, environmental friendliness and low cost. It can effectively promote the oxidative degradation of organic pollutants, improve the COD removal rate, and has good stability, reducing the loss of active metals and the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657193A_ABST
    Figure CN119657193A_ABST
Patent Text Reader

Abstract

The invention relates to an N-doped self-supporting porous calcium sphere ozonation catalyst, the catalyst is composed of network-shaped porous carbon spheres, and metal active components and non-metal active components dispersed on the network-shaped porous carbon spheres, the network-shaped porous carbon spheres are formed by roasting calcium alginate gel at high temperature, and the metal active components and the non-metal active components are dispersed on the network-shaped porous carbon spheres. The metal active component is a calcium compound, and the non-metal active component is a nitrogen compound and a silicon compound; the catalyst is designed and synthesized based on a cross-linking polymerization instantaneous balling principle of sodium alginate and Ca < 2 + >, and particularly, an auxiliary agent and an N source are introduced into a sodium alginate solution, so that the catalyst is further functionalized, and metal-nonmetal synergistic catalysis is realized. The preparation method of the catalyst is simple in technological process, the catalyst can be rapidly prepared in the crosslinking-roasting process, and the catalyst has good catalytic performance and catalyst stability in deep treatment of salt-containing organic wastewater and is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and relates to an N-doped self-supporting porous calcium sphere ozone oxidation catalyst for deep treatment of saline organic wastewater, and a preparation method and application thereof. Background Art

[0002] With the development of human civilization, people's environmental awareness has gradually increased, and countries have increasingly stringent requirements for water pollutant emissions. The progress of production processes and water-saving and energy-saving technologies has resulted in wastewater containing not only organic matter, but also Cl - 、SO4 2- 、Na + PO4 3- Printing and dyeing wastewater, coking wastewater, papermaking wastewater, etc. are all salt-containing organic wastewaters, which have the characteristics of high salt content, complex composition, and high toxicity, and seriously threaten the safety of the water environment. Therefore, its deep treatment has important environmental value and social significance.

[0003] The most widely used pretreatment method for saline organic wastewater is biological treatment, which has a certain effect on reducing the chromaticity and COD of wastewater, but it is difficult to effectively remove the refractory organic matter in the saline state. The excessive accumulation of refractory organic intermediates and the inorganic salt state will inhibit the activity of microorganisms and cannot achieve the expected treatment effect. Therefore, a deep treatment technology for saline organic wastewater with strong pertinence, good treatment effect and high efficiency is needed. At present, the deep treatment technologies for saline organic wastewater mainly include membrane treatment technology, advanced oxidation technology (AOPs), bioaugmentation technology, etc. Among them, AOPs is an effective treatment technology for removing refractory organic pollutants in water. Among various AOPs, heterogeneous catalytic ozonation is a powerful water purification technology that degrades pollutants through the effective oxidation of ozone molecules and reactive oxygen species (ROS) generated by ozone activation.

[0004] The types of catalysts in heterogeneous catalytic ozone oxidation technology mainly include metal-based catalysts and non-metallic carbon-based catalysts. Among them, metal-based catalysts are the most widely used due to their good catalytic activity and low cost. x O y@Al2O3 iron-based composite catalyst, with alumina as carrier, urea as self-sacrificial template, iron oxide loaded on the surface of alumina, the presence of urea helps Fe precipitate on the carrier, and the preparation method significantly improves the dispersibility of Fe. And the catalyst disclosed in the patent increases the COD removal rate of coal chemical wastewater from 43±0.5% of pure ozone oxidation to 80±2.5%, with good wastewater treatment effect. For another example, Jianlong Wang et al. (HaiChen, Jianlong Wang.MOF-derived Co3O4-C@FeOOH as an efficient catalyst for catalytic ozonation of norfloxacin.Journal of Hazardous Materials, 2021, 403, 123697) designed and synthesized Co3O4-C@FeOOH composite catalyst, which can promote O3 decomposition to generate more hydroxyl radicals (·OH), compared with single ozone treatment, TOC removal rate increased from 25.6% to 56.7%. Although metal-based catalysts have achieved good results in wastewater treatment, there are also problems such as catalyst instability and metal leaching during long-term use. Therefore, modification methods such as coating and heteroatom doping are needed to increase the activity and stability of the catalyst. N is considered to be a non-metallic element that can effectively improve the activity and stability of the catalyst. It can regulate the coordination environment of the metal active site to form a metal-nitrogen-carbon (MNC) structure with unique functions. Among them, the type of N and the coordination environment of the metal play an important role in the performance of the catalyst. The types of N mainly include pyridine-N, pyrrole-N, graphite-N and oxide-N. Studies have shown that graphite N can regulate the surface charge distribution of the catalyst and improve the charge transfer ability between the catalyst and the adsorbate, which is beneficial to promote the adsorption and activation of O3 molecules.

[0005] At present, the preparation methods of N-doped metal-based catalysts are mostly supported, which requires the introduction of a N source on the carrier first, and then the loading of active metals, which is a relatively complicated process. At the same time, the metal active components are mostly transition metals or metal oxides. If trace amounts of leaching occur during the long-term ozone catalytic oxidation process, the accumulation of leached elements in water will cause secondary pollution, which is harmful to the water environment. Therefore, it is urgent to design and synthesize an ozone catalyst that is simple to operate, green, efficient, economical and cheap to replace conventional supported transition metal-based catalysts. Summary of the invention

[0006] The purpose of the present invention is to provide an N-doped self-supporting porous calcium sphere ozone oxidation catalyst in view of the problems existing in the prior art; compared with the traditional N-doped modified catalyst, the catalyst has 2+By introducing non-metals during the cross-linking process with sodium alginate, non-metal modification and metal loading are achieved simultaneously, forming porous calcium spheres with a self-supporting network structure and metal-non-metal synergistic catalytic active centers distributed on the porous calcium spheres, which have the advantages of high catalytic activity, environmental friendliness, and low cost.

[0007] To this end, the first aspect of the present invention provides an N-doped self-supporting porous calcium sphere ozone oxidation catalyst, which is composed of a network-like porous carbon sphere, and metal active components and non-metal active components dispersed on the network-like porous carbon sphere; wherein the network-like porous carbon sphere is formed by high-temperature calcination of calcium alginate gel, the metal active component is a calcium compound, and the non-metal active component is a nitrogen compound and a silicon compound.

[0008] In some embodiments of the present invention, the network-like porous calcium spheres are composed of Ca 2+ Ions are cross-linked and polymerized with sodium alginate to form gel beads, which are formed by freeze drying and high temperature calcination, and the diameter of which is 2-5 mm. Preferably, the Ca 2+ In the cross-linking process between ions and sodium alginate, an auxiliary agent and a nitrogen source are also added; further preferably, the auxiliary agent includes one or more of liquid silica gel, phenolic resin and starch. The nitrogen source includes one or more of polyimide, urea, melamine and dopamine.

[0009] Preferably, the specific surface area of ​​the N-doped self-supporting porous calcium sphere ozone oxidation catalyst is 20-200 m 2 / g, pore size is 2-40nm, pore volume is 0.02-0.5cm 3 / g.

[0010] The second aspect of the present invention provides a method for preparing the N-doped self-supporting porous calcium sphere ozone oxidation catalyst according to the first aspect of the present invention, which comprises:

[0011] Step A, adding an auxiliary agent and a nitrogen source to a sodium alginate aqueous solution, and stirring the solution until the solution is uniformly mixed to obtain a sodium alginate-N source mixed solution;

[0012] Step B, adding the sodium alginate-N source mixed solution dropwise into the Ca2+ aqueous solution, cross-linking into balls, filtering, washing, and obtaining calcium-based gel balls;

[0013] Step C, freeze-drying the calcium-based gel beads to obtain a catalyst precursor;

[0014] Step D, calcining the catalyst precursor to obtain an N-doped self-supporting porous calcium sphere ozone oxidation catalyst.

[0015] According to the method of the present invention, the concentration of the sodium alginate aqueous solution is 0.5wt%-4wt%; and / or, Ca 2+ Ca in aqueous solution2+ The concentration is 0.01-5.0mol / L.

[0016] In some embodiments of the present invention, in step A, the mass ratio of the sodium alginate to the auxiliary agent is 1:(5-30); preferably, the auxiliary agent includes one or more of liquid silica gel, starch and phenolic resin.

[0017] In some embodiments of the present invention, in step A, the mass ratio of the sodium alginate to the N source is 1:(2-50); preferably, the N source includes one or more of polyimide, urea, melamine and dopamine.

[0018] According to the present invention, in step C, the freeze-drying temperature is -65°C to -40°C, and the freeze-drying time is 3-9h.

[0019] According to the present invention, in step D, calcination is carried out under an inert gas atmosphere; preferably, the calcination temperature is 400-1000° C.; and / or the calcination time is 0.5-8 h.

[0020] The third aspect of the present invention provides the use of the N-doped self-supporting porous calcium sphere ozone oxidation catalyst as described in the first aspect of the present invention or the N-doped self-supporting porous calcium sphere ozone oxidation catalyst prepared by the preparation method described in the second aspect of the present invention in the deep treatment of saline organic wastewater.

[0021] Preferably, the application includes loading an ozone oxidation catalyst into a wastewater treatment device, introducing wastewater and ozone, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

[0022] In some embodiments of the present invention, the reaction conditions of the ozone oxidation treatment are: COD of the wastewater: 80-300 mg / L, TDS: 3000-5000 mg / L, pH: 2-11, ozone flow rate of 0.01-0.20 L / min, catalyst loading amount of 50-200 g / L, reaction time of 10-180 min, and ozone addition ratio of 0.2-6.0.

[0023] The beneficial effects of the present invention mainly include the following two aspects:

[0024] (I) The N-doped self-supporting porous calcium sphere ozone oxidation catalyst proposed in the present invention does not require additional carrier support. The porous carbon network formed by high-temperature calcination of sodium alginate can provide support for the loading of calcium oxide sites. The porous carbon network has strong hydrophobicity and good adsorption capacity for organic pollutants, which can effectively promote the oxidative degradation of organic pollutants. Compared with traditional supported metal-based catalysts, this catalyst has the advantages of high catalytic activity, environmental friendliness, and low cost.

[0025] (ii) Based on sodium alginate and Ca 2+ The metal-non-metal dual-site catalyst is synthesized in situ during the cross-linking process. The advantage of this catalyst is that the metal calcium site and the non-metal nitrogen site can be constructed simultaneously. N doping can adjust the electronic structure of the carbon adjacent to nitrogen, stimulate non-radical pathways, and enhance the electron transfer process between organic matter, O3 and the catalyst, thereby accelerating the decomposition of organic matter. At the same time, the introduction of N sites can provide adsorption / catalytic active sites and metal bonding sites, reducing the loss of active metals. In particular, the mechanical strength of the catalyst is significantly enhanced while the N source is introduced, which is crucial to improving the stability and service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings:

[0027] Figure 1 COD removal rates of catalysts prepared with different SA:PI:LSR ratios.

[0028] Figure 2 COD removal rate of catalysts prepared with different calcium ion concentrations. DETAILED DESCRIPTION

[0029] To make the present invention easy to understand, the present invention will be described in detail below in conjunction with the accompanying drawings and examples. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.

[0030] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.

[0031] I. Terminology

[0032] The term "TDS" (Total dissolved solids) used in the present invention is also called the total amount of dissolved solids, and is measured in milligrams per liter (mg / L), which indicates how many milligrams of dissolved solids are dissolved in 1 liter of water. The higher the TDS value, the more dissolved substances are contained in the water. Total dissolved solids refer to the total amount of all solutes in the water, including both inorganic and organic substances. Generally, the conductivity value can be used to roughly understand the salt content in the solution. Generally, the higher the conductivity, the higher the salt content, and the higher the TDS. Therefore, TDS also reflects the salt level in the wastewater.

[0033] The term "salt-containing organic wastewater" in the present invention refers to wastewater that contains a large amount of inorganic salts, such as Cl - 、SO4 2- PO4 3- Plasma.

[0034] The term "deep wastewater treatment" mentioned in the present invention generally refers to the further treatment of residual organic matter in the Class II effluent after biochemical treatment by using advanced oxidation technology.

[0035] The term "water" in the present invention, unless otherwise specified or limited, refers to deionized water, ultrapure water or distilled water.

[0036] II. Implementation Plan

[0037] Existing heterogeneous ozone oxidation catalysts still have some shortcomings, for example, the problem of metal component loss, especially the formation of heavy metal ion pollution, will bring difficulties to subsequent treatment; at the same time, the current ozone oxidation catalysts have selective degradation of some difficult-to-degrade new pollutants or organic matter containing special functional groups, so it is necessary to develop specific catalysts to specifically degrade a certain type of wastewater. In addition, the currently widely used supported metal-based catalysts need to be supported by a carrier and have relatively high requirements for the carrier, such as a large specific surface area and rich pore structure; the carrier pretreatment process is complicated, the catalyst preparation cycle is long, and the operating cost is high. These are the problems existing in the current supported metal-based catalysts.

[0038] Although N-doped metal-based catalysts are beneficial for promoting the adsorption and activation of O3 molecules, the existing preparation methods of N-doped metal-based catalysts are mostly supported, requiring the introduction of an N source on the carrier first, and then the loading of active metals, and the process is relatively complicated. At the same time, the metal active components are mostly transition metals or metal oxides. If trace amounts of leaching occur during the long-term ozone catalytic oxidation process, the accumulation of leached elements in the water will cause secondary pollution, which is harmful to the water environment. Therefore, it is urgent to design and synthesize an ozone catalyst that is simple to operate, green and efficient, and economical to replace conventional supported transition metal-based catalysts. In view of this, the inventors have conducted extensive and in-depth research on N-doped metal-based catalysts and their ozone oxidation technology for deep treatment of saline organic wastewater.

[0039] The inventors have found that based on sodium alginate and Ca 2+Ionic crosslinking can form a green and efficient metal-nonmetal dual-site N-doped self-supporting porous calcium sphere ozone oxidation catalyst. Different from the traditional supported N-doped catalyst, the N element and the active metal component grow synchronously in the self-supporting network, avoiding the traditional complex steps of first modifying the carrier and then loading the metal. It has the advantages of simple preparation process, environmental friendliness, economic efficiency, etc., and can be used for the deep treatment of salt-containing organic wastewater. The catalyst obtained by this preparation method has good catalytic performance, high catalytic efficiency, good stability, and can be recycled repeatedly.

[0040] Therefore, the N-doped self-supporting porous calcium sphere ozone oxidation catalyst for deep treatment of saline organic wastewater involved in the first aspect of the present invention is composed of a network-like porous carbon sphere, and metal active components and non-metal active components supported on the network-like porous carbon sphere, wherein the network-like porous carbon sphere is formed by high-temperature calcination of calcium alginate gel, the metal active component is a calcium compound, and the non-metal active component is a nitrogen compound and a silicon compound.

[0041] Based on the above, it is not difficult to understand that the self-supporting porous calcium sphere catalyst is composed of Ca 2+ Ions are cross-linked with sodium alginate to form gel spheres, which are formed by freeze drying and high temperature calcination, and the diameter of the spheres is 2-5 mm; and the Ca 2+ A nitrogen source is also added during the cross-linking process between the ions and the sodium alginate; preferably, the nitrogen source includes one or more of polyimide, urea, melamine and dopamine.

[0042] Preferably, the Ca 2+ Auxiliary agents are also added during the cross-linking process between ions and sodium alginate; further preferably, the auxiliary agent includes one or more of liquid silica gel, phenolic resin and starch.

[0043] The inventors have found that N-doped self-supporting metal-based catalysts, such as N-doped porous calcium sphere catalysts, can achieve the simultaneous introduction of N source and metal active components, without the need for a loading step, with adjustable catalyst size, low cost, simple preparation process, and good application potential. During the pyrolysis process, nitrogen atoms and active metal components grow synchronously in the self-supporting calcium sphere network, actively forming MO / MN x Stable structure. And by adjusting the pyrolysis temperature, the conversion between different types of N can be achieved. In particular, the diameter of the traditional supported N-doped metal-based catalyst particles used for deep treatment of saline organic wastewater is mostly 3-5mm, and the catalyst particles are piled up to form a fixed bed reactor, and the catalyst particles in contact with each other have some active sites covered. The N-doped self-supporting metal-based catalyst has an adjustable size, which can achieve uniform dispersion of catalyst particles in the water body to form a fluidized bed reactor, significantly improving the mass transfer efficiency of the catalytic ozone oxidation process.

[0044] The research results show that the specific surface area of ​​the self-supporting porous calcium sphere catalyst provided by the present invention is 20-200m 2 / g, pore size is 2-40nm, pore volume is 0.02-0.5cm 3 / g.

[0045] The second aspect of the present invention relates to a method for preparing the self-supporting porous calcium sphere ozone oxidation catalyst as described in the first aspect, comprising the following steps:

[0046] (1) Dissolve sodium alginate powder in ultrapure water and shake in a shaker at 60°C until the sodium alginate is completely dissolved to obtain a sodium alginate aqueous solution; dissolve calcium chloride in ultrapure water to obtain a solution containing Ca 2+ of calcium chloride aqueous solution.

[0047] (2) adding an auxiliary agent and a nitrogen source to the sodium alginate aqueous solution, and stirring the solution until the solution is uniformly mixed to obtain a sodium alginate-nitrogen source mixed solution;

[0048] (3) Place the sodium alginate-N source mixture in a separatory funnel, adjust the piston of the separatory funnel, and drip the sodium alginate-N source mixture into the Ca-containing solution at a uniform speed through the bottom of the separatory funnel. 2+ In a calcium chloride aqueous solution, cross-linking into balls, filtering, washing, and obtaining calcium-based gel balls;

[0049] (4) freeze-drying the calcium-based gel beads to obtain a catalyst precursor;

[0050] (5) The catalyst precursor is calcined to obtain an N-doped self-supporting porous calcium sphere ozone oxidation catalyst.

[0051] The present invention is based on sodium alginate and Ca 2+ Ionic cross-linking forms green and efficient N-doped self-supporting porous calcium sphere ozone oxidation catalyst, therefore, it is necessary to investigate and determine the optimal preparation conditions.

[0052] The research results show that in step (1), the concentration of the sodium alginate aqueous solution is 0.5wt%-4wt%, and the concentration of Ca in the calcium chloride aqueous solution is 2+ When the concentration is 0.01-5.0mol / L, sodium alginate and Ca 2+ The gel beads formed by cross-linking polymerization have the best mechanical properties.

[0053] Studies have found that in step (2), adding a N source to the sodium alginate solution can enhance the mechanical strength of the catalyst beads and introduce N active sites. Preferably, the mass ratio of the sodium alginate to the N source is 1:(2-50); further preferably, the N source includes one or more of polyimide, urea, melamine and dopamine.

[0054] In some embodiments of the present invention, in step (2), the mass ratio of the sodium alginate to the auxiliary agent is 1:(5-30); preferably, the auxiliary agent includes one or more of liquid silica gel, starch and phenolic resin.

[0055] In some embodiments of the present invention, in step (4), the calcium-based gel beads are freeze-dried to form pores, the freeze-drying temperature is -65°C to -40°C, and the freeze-drying time is 3-9 hours.

[0056] According to the method of the present invention, in step (5), the catalyst is calcined under an inert gas atmosphere to carbonize and form metal active sites and non-metal active sites; preferably, the calcination temperature is 400-1000° C.; and / or the calcination time is 0.5-8 h.

[0057] The research results show that the N-doped self-supporting catalyst prepared by the method of the present invention is different from the traditional supported N-doped catalyst. The N element and the active metal component grow synchronously in the self-supporting network, avoiding the traditional complex steps of first modifying the carrier and then loading the metal. It is a new method for preparing a simple N-doped self-supporting catalyst. In addition, the catalyst has a COD removal rate of more than 70% for high-salinity organic wastewater and has a good ability to treat high-salinity wastewater.

[0058] The third aspect of the present invention involves the use of the N-doped self-supporting porous calcium sphere ozone oxidation catalyst as described in the first aspect of the present invention or the ozone oxidation catalyst prepared by the preparation method as described in the second aspect of the present invention in the deep treatment of saline organic wastewater, which can be understood as a method for deep treatment of saline organic wastewater using the N-doped self-supporting porous calcium sphere ozone oxidation catalyst as described in the first aspect of the present invention or the N-doped self-supporting porous calcium sphere ozone oxidation catalyst prepared by the preparation method as described in the second aspect of the present invention.

[0059] Preferably, the application includes loading an ozone oxidation catalyst into a wastewater treatment device, introducing wastewater and ozone, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

[0060] The salt-containing organic wastewater in the present invention includes but is not limited to biochemical effluent from chemical industrial parks and / or petrochemical wastewater.

[0061] In some embodiments of the present invention, the reaction conditions of ozone oxidation treatment are: COD: 130-140 mg / L, TDS: 5000-5500 mg / L, pH = 3-10, ozone flow rate of 0.03 L / min, reaction time of 60 min, catalyst loading of 50-200 g / L, reaction time of 10-180 min, and ozone addition ratio of 0.2-6.0.

[0062] The present invention provides an N-doped self-supporting porous calcium sphere ozone oxidation catalyst for deep treatment of saline organic wastewater and a preparation method thereof. 2+ Based on the principle of instant sphering by cross-linking polymerization, a self-supporting porous spherical catalyst was designed and synthesized. In particular, an additive and a N source were introduced into the sodium alginate solution to further functionalize the catalyst and realize metal-nonmetal synergistic catalysis. The structure of the catalyst includes a network-like porous carbon sphere and metal and nonmetal sites distributed on the network-like porous carbon sphere. The above-mentioned catalyst prepared by the present invention has a simple process flow, and the cross-linking-calcination process can realize the rapid preparation of the catalyst. In the deep treatment of salt-containing organic wastewater, it has good catalytic performance and catalyst stability, and is suitable for industrial promotion.

[0063] Example

[0064] The present invention is further described in detail below through the accompanying drawings and specific examples. The experimental methods described below, unless otherwise specified, are all routine laboratory methods. The experimental materials described below, unless otherwise specified, can all be obtained from commercial channels.

[0065] In the following examples, COD was determined by digestion using Hach COD reagent on a Hach DRB200 digestion instrument (Hach Company, USA), and then measured using a DR5000 UV spectrophotometer (Hach Company, USA). TDS was determined using a DDSJ-319L conductivity meter (Shanghai Leici Instrument Co., Ltd.). COD removal rate was calculated according to the following formula:

[0066] COD removal rate = (COD 原始 -COD 氧化后 ) / COD 原始 ×100%

[0067] Embodiment 1:

[0068] (1) preparing 50 mL of a 2.0 wt% sodium alginate aqueous solution, and dissolving calcium chloride in ultrapure water to obtain a calcium chloride (CaCl2) aqueous solution with a concentration of 0.16 mol / L;

[0069] (2) according to the mass ratio of sodium alginate to polyimide being 1:1.5 and the mass ratio of sodium alginate to liquid silica gel being 1:(5-25), sodium alginate, polyimide (N source) and 30% liquid silica gel (auxiliary agent) are mixed, and the solution is fully stirred until it is uniform to obtain a sodium alginate-N source mixed solution;

[0070] (3) placing the sodium alginate-N source mixed solution in a separatory funnel, gradually adding it dropwise into the CaCl2 aqueous solution, cross-linking into balls, filtering and washing with water to obtain calcium-based gel balls;

[0071] (4) placing the calcium-based gel beads in a freeze dryer at -50°C for 7 hours to obtain a catalyst precursor;

[0072] (5) The catalyst precursor was placed in an inert gas atmosphere in a tubular furnace and calcined at 850° C. for 2 h to obtain an N-doped calcium-based porous carbon sphere catalyst.

[0073] Reaction conditions: biochemical effluent from chemical park, COD: 130-140 mg / L, TDS: 5000-5500 mg / L, pH=7, ozone flow rate of 0.03 L / min, reaction time of 60 min, and ozone concentration of 12 mg / L.

[0074] The experimental results show that the COD removal rate of the prepared N-doped self-supporting porous calcium sphere ozone oxidation catalyst is between 55-75%.

[0075] Embodiment 2:

[0076] (1) preparing 50 mL of a 2.0 wt% sodium alginate aqueous solution, and dissolving calcium chloride in ultrapure water to obtain a calcium chloride aqueous solution with a concentration of 0.05-0.30 mol / L;

[0077] (2) mixing sodium alginate and polyimide in a mass ratio of 1:1.5 and a mass ratio of sodium alginate to liquid silica gel of 1:20, adding 30% liquid silica gel, and stirring until the solution is uniform to obtain a sodium alginate-N source mixed solution;

[0078] (3) placing the sodium alginate-N source mixed solution in a separatory funnel, gradually adding it dropwise into a 0.05-0.30 mol / L CaCl2 solution, cross-linking into spheres, filtering and washing with water to obtain calcium-based gel spheres;

[0079] (4) placing the calcium-based gel beads in a freeze dryer at -50°C for 7 hours to obtain a catalyst precursor;

[0080] (5) The catalyst precursor was placed in an inert gas atmosphere in a tubular furnace and calcined at 850° C. for 2 h to obtain an N-doped calcium-based porous carbon sphere catalyst.

[0081] Reaction conditions: biochemical effluent from chemical park, COD: 130-140 mg / L, TDS: 5000-5500 mg / L, pH=7, ozone flow rate of 0.03 L / min, reaction time of 60 min, and ozone concentration of 12 mg / L.

[0082] The experimental results show that the COD removal rate of the prepared N-doped self-supporting porous calcium sphere ozone oxidation catalyst is between 60-80%.

[0083] It should be noted that the embodiments described above are only preferred embodiments of the present invention, which are used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. An N-doped self-supporting porous calcium sphere ozone oxidation catalyst, which is composed of a network-like porous carbon sphere, and a metal active component and a non-metal active component dispersed on the network-like porous carbon sphere; wherein: The network-shaped porous carbon spheres are formed by high-temperature calcination of calcium alginate gel, the metal active components are calcium compounds, and the non-metal active components are nitrogen compounds and silicon compounds.

2. The N-doped self-supporting porous calcium sphere ozone oxidation catalyst according to claim 1, characterized in that: The N-doped self-supporting porous calcium sphere ozone oxidation catalyst is composed of Ca 2+ The calcium alginate gel spheres are cross-linked with sodium alginate and then freeze-dried and calcined at high temperature to form a 2-5 mm diameter calcium alginate gel sphere. 2+ Auxiliary agents and nitrogen sources are also added during the cross-linking process with sodium alginate; further preferably, the auxiliary agent includes one or more of liquid silica gel, starch and phenolic resin; the nitrogen source includes one or more of polyimide, urea, melamine and dopamine.

3. The N-doped self-supporting porous calcium sphere ozone oxidation catalyst according to claim 1 or 2, characterized in that: The specific surface area of ​​the N-doped self-supporting porous calcium sphere ozone oxidation catalyst is 20-200 m 2 / g, pore diameter is 2-40nm, pore volume is 0.02-0.5cm 3 / g.

4. The method for preparing the N-doped self-supporting porous calcium sphere ozone oxidation catalyst according to any one of claims 1 to 3, comprising: Step A, adding an auxiliary agent and a nitrogen source to a sodium alginate aqueous solution, and stirring the solution until the solution is uniformly mixed to obtain a sodium alginate-N source mixed solution; Step B: Add the sodium alginate-N source mixed solution dropwise to the Ca 2+ In aqueous solution, cross-linking into balls, filtering, washing, and obtaining calcium-based gel balls; Step C, freeze-drying the calcium-based gel beads to obtain a catalyst precursor; Step D, calcining the catalyst precursor to obtain an N-doped self-supporting porous calcium sphere ozone oxidation catalyst.

5. The preparation method according to claim 4, characterized in that: The concentration of the sodium alginate aqueous solution is 0.5wt%-4wt%; and / or, Ca 2+ Ca in aqueous solution 2+ The concentration is 0.01-5.0mol / L.

6. The preparation method according to claim 4, characterized in that: In step A, the mass ratio of the sodium alginate to the auxiliary agent is 1:(5-30); preferably, the auxiliary agent includes one or more of liquid silica gel, starch and phenolic resin; And / or, the mass ratio of the sodium alginate to the N source is 1:(2-50); preferably, the N source includes one or more of polyimide, urea, melamine and dopamine.

7. The preparation method according to claim 4, characterized in that: In step C, the freeze-drying temperature is -65°C to -40°C, and the freeze-drying time is 3-9 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step D, calcination is performed under an inert gas atmosphere; preferably, the calcination temperature is 400-1000° C.; and / or the calcination time is 0.5-8 h.

9. Use of the N-doped self-supporting porous calcium sphere ozone oxidation catalyst as described in any one of claims 1 to 3 or the N-doped self-supporting porous calcium sphere ozone oxidation catalyst prepared by the preparation method as described in any one of claims 4 to 8 in the deep treatment of saline organic wastewater; preferably, the application comprises loading the ozone oxidation catalyst in a wastewater treatment device, passing wastewater and ozone into the device, performing ozone oxidation treatment on the wastewater, and obtaining oxidized effluent that meets emission standards.

10. The use according to claim 9, characterized in that: The reaction conditions of the ozone oxidation treatment are: COD of the wastewater: 80-300 mg / L, TDS: 3000-5000 mg / L, pH: 2-11, ozone flow rate of 0.01-0.20 L / min, catalyst loading amount of 50-200 g / L, reaction time of 10-180 min, and ozone addition ratio of 0.2-6.0.

Citation Information

Patent Citations

  • Preparation method of modified alumina carrier, palladium catalyst and preparation method thereof

    CN109967132A

  • Calcium-based porous carbon sphere catalyst for deep treatment of salt-containing organic wastewater by catalytic ozonation

    CN115025767A

  • Ca-based catalytic ozonation catalyst for deep treatment of salt-containing organic wastewater and preparation method of Ca-based catalytic ozonation catalyst

    CN115055174A

  • Palladium-based catalyst for synthesizing dimethyl oxalate through CO coupling as well as preparation method and application of palladium-based catalyst

    CN115228502A

  • Material of dopamine-coated porous silicon cross-linked sodium alginate, preparation method and application

    CN116632204A